Paralelos entre el poema de Gilgamesh y el Génesis (caps. III-V y VI-VIII) - Rabanal Alonso, Manuel Abilio (Estudios humanísticos. Geografía, historia y arte, 1991)
There is no doubt that an obvious relationship exists between Genesis and the Poem of Gilgamesh. The Old Testament as a whole contains part of the wisdom of the Middle East. That is the reason for its importance in History.